The use of platelet-rich plasma in anti-aging therapy (overview) - Chorążewska, Małgorzata; Piech, Piotr; Pietrak, Justyna; Kozioł, Maciej; Obierzyński, Paweł; Maślanko, Monika; Wilczyńska, Karolina; Tulwin, Tytus; Łuczyk, Robert (Journal of Education, Health and Sport, 2017)
Introduction Aging stands for the changes in the human body, which are recognized as natural processes that concern every person and are related to the passage of time. Despite ‘normalness’ of the process, a tendency is emerging to treat aging as a pathology requiring proper diagnostics. Consequently, an ‘anti-aging’ medicine has been established - defined as study of preventing and slowing down the process of aging. Aim of the study The aim of this study is to summarize and present the current knowledge, based on the overview of writing on the properties and effectiveness of the use of PRP in anti-aging therapy. Description of knowledge Autologous platelet-rich plasma is a concentrate of human blood platelets suspended in a small amount of plasma, wherein concentration of thrombocytes is higher than initial concentration. For autologous plasma to have high healing properties, platelet levels should be at least 1 million in 5 ml of plasma. The basic condition for initiating repair and regenerative processes in vivo is the formation of a blood clot. Also, by degranulating, platelets release many growth factors, such as PDGF, TGF-β, EGF, FGF, VEGF and others, which are involved not only in blood coagulation, but also in immune response and tissue healing. The large variety of PRP-obtaining methods and the range of concentration levels of growth factors in PRP may lead to ambiguity in the literature, as to the extent to which formulation was actually used in a variety of preclinical and clinical studies. Some of those studies are presented in this article. Summary Platelet-rich treatments are part of the growing popularity of regenerative medicine, which is beginning to be recognized as the medicine of the future. However, without proper control methods or optimization of numerous variables (e.g. concentration or ratio of growth factors) during PRP preparation, it is not known which ingredients are needed and preferred, and which are harmful for tissue regeneration. However, numerous studies show PRP injection as a promising method of rejuvenating the skin, therefore platelet-rich treatments are an important part of the growing popularity of regenerative medicine.